A synchronised multi-motor control system using hybrid sensorless induction motor drives - Turl, Gary (2002)
The main aim of this project was to research, develop and test an induction motor drive not requiring a speed encoder, but which could be considered commercially viable by motor drives manufacturers, and which should aim to meet the follow requirements: